Brucite – Industrial Mineral with a Future - Simandl, George; Paradis, Suzanne; Irvine, Melanie (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2007)
Brucite, Mg(OH)2, is an uncommon mineral primarily known to mineral collectors, and to specialists studying contact metamorphic and ultramafic rocks. It is an environmentally friendly flame-retardant and is in commercial demand; it also represents a potential ore source for the metal, magnesium, which is itself in great demand. The present brucite market for flame-retardants is less than 50 000 tonnes annually, but it is increasing exponentially. Brucite has the advantage of not containing CO2; hence none is released during calcination, a positive feature in today’s society concerned with climate change. This review paper summarises the topic for scientists studying the thermodynamic properties of brucite, geologists studying its contact meta-morphic characteristics, exploration geologists and potential end-users. Given the demand for the mineral and metal, high-grade brucite deposits may become hot exploration targets within the next few years.